Alpha-fetoprotein–producing recurrent nasopharyngeal carcinoma: A case report. (November 2021) - Yang, Zhen-Chong; Luo, Mei-Juan; Liu, Li-Li; Cai, Mu-Yan; Liang, Yu-Jing; Chen, Qiu-Yan; Tang, Lin-Quan; Mai, Hai-Qiang
Alpha-fetoprotein hardly increased due to nasopharyngeal cancer. In this article, we reported a 57-year-old male nasopharyngeal carcinoma patient who had posttreatment subscapular metastasis with high serum alpha-fetoprotein but negative plasma Epstein–Barr virus DNA. Pathology results indicated that the scapular mass was undifferentiated non-keratinizing carcinoma originated in the nasopharynx. Moreover, no liver lesion was detected by imaging examination. In view of the positive alpha-fetoprotein and alpha-fetoprotein messenger RNA staining result in the right scapular mass fine needle aspiration biopsy sample, we considered the diagnosis of alpha-fetoprotein-producing nasopharyngeal carcinoma that had never been reported before.